Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1124/jpet.105.090803
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Cardioprotection against Ischemia/Reperfusion Injury in Adult Rat Hearts: Focus on Akt and Protein Kinase C Signaling

Abstract: Previous studies have reported the sex differences in heart susceptibility to ischemia/reperfusion (I/R) injury, but the mechanisms are not understood. The present study tested the hypothesis that Akt and protein kinase C (PKC)⑀ play an important role in the sexual dimorphism of heart susceptibility to I/R injury. Isolated hearts from 2-month-old male and female rats were subjected to I/R in the Langendorff preparation. The postischemic recovery of left ventricular function was significantly better, and infarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
111
3
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(140 citation statements)
references
References 39 publications
(51 reference statements)
21
111
3
5
Order By: Relevance
“…In I/R models, intact premenopausal female rodents compared with males have reduced injury as evidenced by smaller infarct size and greater recovery after I/R (16,17). Acute and/or chronic E2 supplementation provided protection both in isolated perfused hearts undergoing global ischemia and in in vivo ligation of the left anterior descending coronary artery (18,19).…”
Section: Estrogen and Sex Differences In Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In I/R models, intact premenopausal female rodents compared with males have reduced injury as evidenced by smaller infarct size and greater recovery after I/R (16,17). Acute and/or chronic E2 supplementation provided protection both in isolated perfused hearts undergoing global ischemia and in in vivo ligation of the left anterior descending coronary artery (18,19).…”
Section: Estrogen and Sex Differences In Cardiovascular Diseasementioning
confidence: 99%
“…Acute and/or chronic E2 supplementation provided protection both in isolated perfused hearts undergoing global ischemia and in in vivo ligation of the left anterior descending coronary artery (18,19). The exact mechanism is unknown, but it has been shown that females exhibit greater activation of AKT and protein kinase C (PKC) epsilon, and inhibition of either of these pathways led to the loss of protection in females, but had no effect on males (20). Both ER α and β have been shown to mediate the protective effects in I/R injury (21,22).…”
Section: Estrogen and Sex Differences In Cardiovascular Diseasementioning
confidence: 99%
“…For example, in an in vitro, global ischemia-reperfusion model using Langendorff-perfused rat hearts, Bae and Zhang observed significantly less myocardial injury in female vs. male hearts (23% relative reduction) following 25 minutes of ischemia and 2 hours of reperfusion. [22] Pharmacologic inhibitor experiments further showed that reduced myocardial injury in females was dependent on the phosphatidylinositol-3 kinase and protein kinase C epsilon (PKCε) signaling pathways. Brown et al [23] demonstrated in a similar model that protection from injury in females was dependent on functional sarcolemmal K ATP channels.…”
Section: Myocardial Injury Modelsmentioning
confidence: 99%
“…It has been elucidated in rats that females have greater resistance to cardiac IR injury than males through the effect of estrogen, 29 and that treatment with estrogen mitigates cardiac IR injury in ovariectomized rats. 30 In the present study, longterm treatment with TJ-113 did not affect plasma estrogen levels in the ovariectomized rats, suggesting that the beneficial effects of TJ-113 on the IR injury in the ovariectomized rats were not related to changes in plasma estrogen levels.…”
Section: No Involvement Of Estrogen In the Beneficial Effects Of Tj-1mentioning
confidence: 99%